The State of the Field: Results from the 2014 and 2017 Pediatric Rehabilitation Medicine Practice Surveys. Issue 2 (30th September 2019) - Houtrow, Amy J.; Zigler, Christina K.; Pruitt, David W.
Abstract : Background: Childhood disability is on the rise and there is a national shortage of pediatric physiatrists in the United States. The 2009 Pediatric Rehabilitation Medicine Practice Survey identified concerns regarding inadequate geographic dispersion of providers, salary inequities, and limited academic competitiveness and external funding for research. Objective: To describe the current state of the field of pediatric rehabilitation medicine. Design: Survey of pediatric physiatrists in the United States in 2014 and 2017. Setting: National. Participants: Pediatric physiatrists Interventions: Not applicable. Main Outcome Measurements: Characteristics; clinical activities, responsibilities, and comfort; academic activities; and salaries and productivity. Results: In both 2014 and 2017, the majority of pediatric physiatrists who responded were women ( 63%) and worked at an academic teaching hospital ( 68%). Pediatric physiatrists most commonly held the title of assistant professor and were overrepresented in the Midwest. Overall, 55.8% of providers felt that access was adequate in their area whereas only 3.7% felt access was adequate across the country. In 2017, 52.5% of pediatric physiatrists participated in research or other scholarly activities with 44.2% reporting having published original research at some point in their careers. The inflation adjusted mean salary in 2014 (227 360) was not statistically different than in 2017 (232 634, P = .422). In both years, full professors reported the highest academic full‐time salaries. Individuals having at least one leadership title also reported significantly higher average full‐time salaries than individuals with no titles. Conclusions: Although gains have been made in terms of academic competitiveness and engagement in research in pediatric physiatry, there are areas of ongoing concern including large geographic practice variations with associated access to care problems, challenges with recruiting physicians to the field, and salary malalignment within the field of PM&R.